Analysis of the cost structure: perspectives from the manufacturing companies in Sri Lanka / Nuwan Gunarathne and Dileepa Samudrage. - Gunarathne, Nuwan; Samudrage, Dileepa (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
The purpose of this paper is to analyse the cost structure of manufacturing companies in an emerging economy. The data was collected from 41 listed manufacturing companies in Sri Lanka mainly through a structured questionnaire and an analysis of company records. In addition, to analysing the data descriptively, we used correlation and regression models. The findings suggest that despite the majority of costs being variable, there are great differences among the companies in the composition of costs. There is no relationship between the cost structure and the level of advanced manufacturing technology used, which suggests a low level of technology related costs in the cost structure. Budgeting and cost control are the main reasons for classifying costs while there is inadequate use of information for strategizing pricing decisions. Differences were also observed in the classification of the manufacturing cost items in the respondent companies. Finally, all the findings confirm that accounting practices in emerging economies are shaped by their environment as well. The study also reveals certain managerial and policy level implications.